A narrative review of morphology of cancellous bone at different human anatomy- methods and parameters - Abdul Rahim, Rabiatul Adibah (2015)
Morphology of cancellous bone has been studied for years, with researchers always seeking accurate methods to assess the parameters. They also study the importance of cancellous morphology in itself. Despite the amount of previous research, there are currently no reviews on the morphology at different anatomy. This paper evaluate the methods and parameters of cancellous bone morphology at different human anatomy. From 1997 to February 2014 we found the articles published on cancellous bone morphology vary in parameters at different anatomy of human bone. Further, researchers are also interested in finding the precision methods for identifying the parameters of cancellous bone. Both in vitro and in vivo were used in finding the accurate result of cancellous bone parameters whilst also searching the importance of the morphology parameters. The morphology studies are vital due to the direct relation with the mechanical properties of cancellous bone. Based on the morphology data, it is found that the morphology parameters are dissimilar at different human anatomy sites. A variety of methods were used by researchers in identifying the morphology parameters, with each method having its own advantages and disadvantages. This review paper summarises the pros and cons of all methods available, in order to help researchers select the best methods for their future studies.